Validation of the Cognitive Fusion Scale in Cuban adults with anxiety symptoms - García Rojas, Pedro; Valdés Santiago, Damian (Interacciones, 2023)
Background: Cognitive Fusion (CF) is a psychological problem that is a fundamental concept within Acceptance and Commitment Therapy. The Cognitive Fusion Scale (CFS), which is used to measure this concept, has not been adapted or validated in Cuba. Objective: To evaluate the psychometric properties of the CFA in adults with anxiety symptoms. Method: Qualitative and quantitative techniques were combined: Expert interview, correlation and concordance coefficients and factor analysis. Result: The CFQ was adapted from a linguistic and cultural perspective. Nine experts were consulted and consensus was assessed using the content validity coefficient of appropriateness (0.97). During piloting with 35 people, the test achieved a Cronbach's α coefficient (0.927). When the adapted test was applied to 106 adults with anxiety symptoms, a Cronbach's α coefficient (0.869) was achieved, demonstrating the homogeneity of the test. The exploratory factor analysis (KMO = 0.820, X2 (338) = 21, p < 0.001) showed item ambiguities of less than 0.6 and factor loadings of more than 0.3. The confirmatory factor analysis showed a good model fit (X2 (14) = 45.1, p < 0.001). A low and statistically significant correlation (Rho = 0.216, p < 0.05) was found in relation to IDARE (state). Conclusion: The adapted CFQ was valid in terms of content, showed high reliability values and its one-dimensionality was verified. The adapted instrument shows a correlation between FC and anxiety symptoms. An instrument like this could improve the diagnosis of CF, as well as increase the quality of care for the patient.